2020
DOI: 10.1002/jcp.29836
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency induced necroptosis, Th1/Th2 imbalance, and inflammatory responses in swine ileum

Abstract: Selenium (Se) deficiency has a significant impact on the swine breeding industry by inducing digestive system damage and diarrhea. However, the molecular mechanism remains unclear. Our objectives were to investigate if different amounts of necroptosis, inflammatory responses, and T helper cell 1/T helper cell 2 (Th1/Th2) imbalances were induced by Se deficiency in intestinal porcine jejunal epithelial cells (IPEC-J2) and swine ileum tissue. Therefore, Se-deficient models were successfully established both in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…Selenoproteins are involved in the regulation of cellular redox homeostasis, and the protection of oxidative stress ( Schomburg and Schweizer, 2009 ). Besides, the study has shown that Se deficiency can change the distribution and steady-state of other minerals, which had been confirmed again in our experiment ( Zhang et al., 2021 ). In this study, we established the Se deficiency model in swine and IPEC-J2 cells, in which results showed that Se deficiency caused a downward trend in the overall selenoproteins expressions and disrupted the balance of intestinal trace elements.…”
Section: Discussionsupporting
confidence: 85%
“…Selenoproteins are involved in the regulation of cellular redox homeostasis, and the protection of oxidative stress ( Schomburg and Schweizer, 2009 ). Besides, the study has shown that Se deficiency can change the distribution and steady-state of other minerals, which had been confirmed again in our experiment ( Zhang et al., 2021 ). In this study, we established the Se deficiency model in swine and IPEC-J2 cells, in which results showed that Se deficiency caused a downward trend in the overall selenoproteins expressions and disrupted the balance of intestinal trace elements.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, our previous research also showed that selenium de ciency did cause in ammation of swine intestinal tissue and IPEC-J2 cells [46]. In our present experiment, it was observed that ROS production in IPEC-J2 cells increased due to selenium de ciency stimulation.…”
Section: Discussionsupporting
confidence: 68%
“…Necroptosis may also support the effector activity of Th17 cells following recognition of fungi. A special case of this is when necroptosis of macrophages in a process called metaphorosis can lead to calcineurin-dependent lateral transfer of A. fumigates to live macrophages to downregulate fungal germination [ 100 , 101 ]. Selenium deficiency induced accelerated cell necroptosis in IPEC-J2 cells, resulting in increased expression of IL-1β, IL-6, IL-7 and IL-17, while the expression of IFNγ, IL-10 and IL-4 is down-regulated indicating a Th17 polarization of helper T cells [ 100 ].…”
Section: Immunological Decision-making Ii: How Do the Different Necro...mentioning
confidence: 99%
“…A special case of this is when necroptosis of macrophages in a process called metaphorosis can lead to calcineurin-dependent lateral transfer of A. fumigates to live macrophages to downregulate fungal germination [ 100 , 101 ]. Selenium deficiency induced accelerated cell necroptosis in IPEC-J2 cells, resulting in increased expression of IL-1β, IL-6, IL-7 and IL-17, while the expression of IFNγ, IL-10 and IL-4 is down-regulated indicating a Th17 polarization of helper T cells [ 100 ]. Intestinal epithelial cell necroptosis, which results in the recruitment and activation of ILC3s and IL-22 production, also enhances Th17 responses [ 102 ].…”
Section: Immunological Decision-making Ii: How Do the Different Necro...mentioning
confidence: 99%